A systematic review of the pharmacokinetic and pharmacodynamic interactions of herbal medicine with warfarin. - Songie Choi; Dal-Seok Oh; Ui Min Jerng (PLoS ONE, 2017)
Objectives The aim of this study was to systematically review data regarding pharmacokinetic (PK)-pharmacodynamic (PD) parameters from randomized controlled trials relating to interactions between herbal medicines and warfarin. Methods Three electronic databases were searched to identify relevant trials. Two reviewers independently performed the study selection and data extraction. The risk of bias and reporting quality were also assessed independently by two reviewers using the Cochrane risk of bias tool and the consolidated standards of reporting trials (CONSORT). Outcomes were measured for all reported PK-PD parameters and adverse events. Results Nine randomized controlled trials met our inclusion criteria. Most of the included studies were unclear regarding the risk of bias and had a low quality of methodology. Using CONSORT, the reporting percentages for the articles ranged from 36.5% to 61.5% and the mean percentage for all articles was 45.6%. St John's wort and echinacea affected the PK parameters of warfarin. Ginseng, ginger, garlic, and cranberry had no significant effect on the PK parameters. American ginseng altered the PD parameters of warfarin. St John's wort, ginseng, Korea red ginseng, ginkgo, ginger, garlic, aged garlic, and echincea did not significantly alter the PD parameters. Studies of ginkgo and cranberry showed conflicting results on the PK parameters and PD parameters, respectively. The incidence of adverse events in all trials was low and no major adverse events were reported. Conclusions It was difficult to determine whether ten herbal medicines had significant effects on the PK-PD parameters of warfarin. Low quality of evidence, different compounds within and different compositions of the herbs, and methodological limitations of the crossover study, which is a clinical study in which subjects receive a sequence of different interventions, made it difficult to form conclusions. Additional studies that remedy these vulnerabilities are necessary to verify these results.